THE BASIS OF NATURAL SCIENCES FOR CHREMATISTIC CONSCIOUSNESS - N. V. Maslova; N. V. Antonenko (Модернизация, инновация, развитие)
The article contains natural-scientific basis of chrematistic consciousness of a person and aimed to use mechanisms of upgrading genetic determinate mind of a person.